Reflections on the state of developing virtual environments - Ray, Andrew (International Journal of Virtual Reality, 2016)
Virtual environments (VEs) demonstrate the immense potential computer technology can provide to society. VEs have been created for almost two decades, but standardized tools and procedures for their creation do not exist. Numerous efforts to create tools for creating VEs have come and gone, but there is little consensus among tool creators for establishing a common subset of standard features that developers can expect. Currently, developers use one of many Virtual Reality (VR) toolkits to create a VE. However, VR toolkits are problematic when it comes to interoperability between applications and other VR toolkits. This paper investigates why the development tools are in this state. A discussion on the history of VR toolkits and developer experiences is used to show what developers face when they create a VE. Next, Three Dimensional Interaction Technique (3DIT) toolkits are introduced to show a new way of developing some parts of VEs. Lastly, a vision for the future of VE development that may help improve the next generation of toolkits is presented.